Ultra-low extracorporeal volume microfluidic leukapheresis is safe and effective in a rat model - Mubasher Iqbal; Alexandra L. McLennan; Anton Mukhamedshin; Mai T. P. Dinh; Qisheng Liu; Jacob J. Junco; Arvind Mohan; Poyyapakkam R. Srivaths; Karen R. Rabin; Thomas P. Fogarty; Sean C. Gifford; Sergey S. Shevkoplyas; et al. (Nature Communications)
Abstract Leukapheresis is a potentially life-saving therapy for children with symptomatic hyperleukocytosis. However, the standard centrifugation-based approach exposes pediatric patients to significant complications due to its large extracorporeal volume, high flow rates, and considerable platelet loss. Here, we tested whether performing cell separation with a high-throughput microfluidic technology could alleviate these limitations. In vitro, our microfluidic devices removed ~85% of large leukocytes and ~90% of spiked leukemic blasts from undiluted human whole blood, while minimizing platelet losses. Multiplexed devices connected in parallel allowed for faster, clinically relevant flow rates in vitro with no difference in leukocyte collection efficiency. When connected to Sprague-Dawley rats, the devices removed large leukocytes with ~80% collection efficiency, reducing the leukocyte count in recirculating blood by nearly half after a 3-hour procedure. Evaluation of plasma biomarkers and end-organ histology revealed no adverse effects compared to sham control. Overall, our study suggests that microfluidics-based leukapheresis is safe and effective at selectively removing leukocytes from circulation, with separation performance sufficiently high to ultimately enable low extracorporeal volume leukapheresis in children.